ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS PADA CV. BORNEO BANGUN NUSA PALEMBANG - Albert Rachmatullah; Lili Syafitri (JURNAL KOMPETITIF, 2018)
The company's financial statements are the result of an accounting process that can be used as a tool for communication with users of financial statements and is also used as a measure of company performance.Company performance is a description of the financial condition of a company that is analyzed with the tools of financial analysis, so it can be known about good bad financial condition of a company that reflects the performance of work within a certain period. The financial performance of a company can be measured and viewed through the financial statements by analyzing the financial statements. Keywords: Financial Reports, Financial Performance